Peranan Teknologi dalam Konvergensi Pertumbuhan Ekonomi antar Daerah Pesisir di Kawasan Timur Indonesia - Tajerin Tajerin (Economic Journal of Emerging Markets, 2007)
The economic growth of Indonesian eastern zone has lower than that of Indonesian western area relatively. Within pushing economic growth, poor region will faster than rich region, income disparity among region in Indonesian Eastern Region will converge. The phenomena also could be seen from comparing among coastal region in the area. The research was aimed to know of technological contribution in converging of economic growth among coastal region in Indonesian eastern area. Data were panel data from period 1975-2002 which were analyzed using Total Factor Productivity (TFP) catch-up model and Technological transferring model. The results show that within TFP model, the difference of technological level among coastal region in Indonesian Eastern Area brought of difference of catching TFP significantly. If the difference of technological level was gone, catching of TFP would show at the faster level and pushing converge at the income level among coastal region in Indonesian Eastern area. Within technological transferring model, most of the convergence come from technological transfer with the difference of technological level among coastal region are widest. If the difference was gone, the technological transfer would be faster and more pushing of income converging among coastal region in Indonesian eastern zone. Keywords: economic growth, eastern indonesia, coastal regions